North Borneo intervarsity Sabah: surgical quiz competition 2023 - Abdul Rashid, Nor Faezan; Che Ani, Mohd Firdaus; Osman, Nora Julianna (Faculty of Medicine, 2023)
On the 2nd and 3rd of June 2023, the Faculty of Medicine University Malaysia Sabah organized a North Borneo Intervarsity Sabah Surgical Quiz Competition in conjunction with the Sabah Surgical Conference 2023, held between the 1st - 4th June 2023. The competition was held in the University Malaysia Sabah, with a total of 6 universities participating, including the Faculty of Medicine UiTM. The other universities were the University Putra Malaysia (UPM), University Science Malaysia (USM), University Malaysia Sabah (UMS), International Medical University (IMU), and SEGi University